1994
DOI: 10.1111/j.1532-950x.1994.tb00476.x
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Biomechanical Investigation of an Interlocking Nail for Fixation of Diaphyseal Tibial Fractures in Adult Horses

Abstract: The compressive, bending and torsional mechanical properties of osteotomized adult equine tibiae stabilized with an interlocking intramedullary nail (nail-tibia composite) were compared with those of intact tibiae to determine the clinical applicability of the the nail for repair of tibial fractures in adult horses. The mean yield load, failure load, and stiffness for the nail-tibia composites were significantly less (P < .05) than those for the intact tibiae in all loading configurations. The mean compressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 24 publications
2
41
0
1
Order By: Relevance
“…The study of bone pairs in which one is a control relative to the other, is consistent with the views of other authors (McClure et al 1994, McClure et al 1994b, McDuffee et al 1994. The choice of which one of them was to be tested for compression and bending was random.…”
Section: Notes On Materials and Methodssupporting
confidence: 83%
“…The study of bone pairs in which one is a control relative to the other, is consistent with the views of other authors (McClure et al 1994, McClure et al 1994b, McDuffee et al 1994. The choice of which one of them was to be tested for compression and bending was random.…”
Section: Notes On Materials and Methodssupporting
confidence: 83%
“…As said, torsion stiffness values for tibia reported by McDuffee et al (1994) can be directly compared to our results. They measured the torsional stiffness over the full length of 380 mm and found stiffness values of 84.15 N*m/°.…”
Section: Discussionmentioning
confidence: 58%
“…This stiffness would be doubled (32.5/23.0)2 =1.99). So we get a value of 2*2.34 kN/mm=4.67 kN/mm for the tibia measured by McDuffee et al 1994. The value for bending stiffness from the study reported by the same author in 1997 are given in Nm/mm.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Auch in den darauffolgenden Jahren wurden weitere Versuche gestartet, diese beim Menschen und Kleintier sehr populäre Frakturbehandlungstechnik beim Pferd einzuführen (Fitch et al 2001). Auch die Entwicklung der Verriegelungsmarknägel machte nicht Halt vor der versuchsweisen Anwendung beim Pferd , Watkins und Ashman 1991, McDuffee et al 1994, Herthel 1996, Radcliffe et al 2001, Galuppo et al 2002b) Von all den getesteten Implantaten, hat sich bis heute nur eines einigermaßen behauptet und wird noch eingesetzt. Es geht auf die Initiative von Jeff Watkins an der Texas A&M Universität zurück und kann erfolgreich bei jüngeren Pferden eingesetzt werden.…”
Section: Marknagelungunclassified